1995
DOI: 10.1063/1.114578
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized light-induced scattering in periodically poled lithium niobate

Abstract: A new species of self-organized light-induced scattering, appearing only in bulk periodically poled lithium niobate, is reported. Clearly defined diffracted beams develop on exposure to 532 nm light from a frequency-doubled, Q-switched, and mode-locked Nd:YAG laser. The structure thus created also diffracts light at 1064 nm. The effect is strongly dependent on temperature, the polarization state of the light, and the period of domain reversal. It exhibits a sharply defined nonlinear threshold at which the far-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A solution to avoid this effect is to increase the intrinsic conductivity of the material (without illumination) by doping it for example with MgO and/or to increase the temperature of the crystal [9]. Another alternative is to balance the ratio of Fe 2+ and Fe 3+ , which is particularly true for the case where the current diffusion is more important.…”
Section: Introductionmentioning
confidence: 99%
“…A solution to avoid this effect is to increase the intrinsic conductivity of the material (without illumination) by doping it for example with MgO and/or to increase the temperature of the crystal [9]. Another alternative is to balance the ratio of Fe 2+ and Fe 3+ , which is particularly true for the case where the current diffusion is more important.…”
Section: Introductionmentioning
confidence: 99%
“…This Kerr-like non-linearity should be taken into account when an intense laser beam is used, which is the case of our experiments, as described above. Besides, the index variation via the EO effect can originate from three phenomena: optical rectification (OR) [49,50], pyroelectric (PE) [51,52] and photo-induced (PI) [53][54][55] effects. The OR might contribute to the total EOs effect because under illumination of PPLT with light polarized parallel to the polar axis, it produces a quasi-static field along this axis direction.…”
Section: On the Origin Of The Second Pair Of Opo2mentioning
confidence: 99%
“…[1][2][3][4] Recently it has been shown that PPLN is attractive not only for frequency doubling but also for photorefractive applications. [5][6][7] The photorefractive response of PPLN is weak for low spatial frequencies of the exciting light interference patterns and strong for sufficiently small periods of the space-charge gratings. This distinctive feature prevents large-scale distortions of light beams ͑optical damage͒ and, at the same time, permits the standard schemes of two-wave and four-wave mixing 8,9 using the advantage of strong photorefractive nonlinearity of lithium niobate.…”
Section: Introductionmentioning
confidence: 99%